2000
DOI: 10.1128/jb.182.24.7021-7028.2000
|View full text |Cite
|
Sign up to set email alerts
|

Functional Expression and Characterization of the Two Cyclic Amidohydrolase Enzymes, Allantoinase and a Novel Phenylhydantoinase, from Escherichia coli

Abstract: A superfamily of cyclic amidohydrolases, including dihydropyrimidinase, allantoinase, hydantoinase, and dihydroorotase, all of which are involved in the metabolism of purine and pyrimidine rings, was recently proposed based on the rigidly conserved structural domains in identical positions of the related enzymes. With these conserved domains, two putative cyclic amidohydrolase genes from Escherichia coli, flanked by related genes, were identified and characterized. From the genome sequence of E. coli, the allB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 47 publications
5
43
1
Order By: Relevance
“…2A, lower panel); once it had reached its maximum value, the spectrum decayed at the same rate as the spontaneous racemization of allantoin (34) (not shown), indicating that the enzyme has an absolute stereospecificity for the S enantiomer of allantoin. The formation of allantoic acid in the reaction catalyzed by PuuE could be unambiguously assessed by NMR spectroscopy using 13 C-labeled (S)-allantoin (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2A, lower panel); once it had reached its maximum value, the spectrum decayed at the same rate as the spontaneous racemization of allantoin (34) (not shown), indicating that the enzyme has an absolute stereospecificity for the S enantiomer of allantoin. The formation of allantoic acid in the reaction catalyzed by PuuE could be unambiguously assessed by NMR spectroscopy using 13 C-labeled (S)-allantoin (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
“…To obtain 13 C NMR spectra of the product of the PuuEcatalyzed reaction, a 1.1-ml solution of 0.1 M potassium phosphate, 80% D 2 O, pD 7.6, containing 15 N, 13 C-labeled (S)-allantoin (6.9 mM) was supplemented with PuuE (0.54 M); the solution was gently stirred for 1 min and then transferred in a 5-mm NMR tube to collect spectra at different times. The 13 C NMR spectra were proton decoupled and were collected at 25°C with a VARIAN Inova 600 instrument.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous EST analysis from the trunk wood of black locust (Yang et al, 2003), we found an EST that was homologous to other reported allantoinase genes such as those found in Escherichia coli (Kim et al, 2000), yeast (Buckholz and Cooper, 1991), and bullfrog (Hayashi et al, 1994). To obtain a full-length cDNA clone, we used 4-to 6-d-old seedlings to construct a cDNA library, and then screened them using the EST as a probe.…”
Section: Allantoinase Genes From Black Locust and Arabidopsismentioning
confidence: 99%